Horngren's Financial & Managerial Accounting : The Managerial Chapters - Miller-Noble, Tracie L., author; Mattison, Brenda, author; Matsumura, Ella Mae 1952-, author (Harlow : Pearson, 2019)
Includes bibliographies and index